Bacterial communities associated with ambrosia beetles: current knowledge and existing gaps - Cambronero-Heinrichs, Juan Carlos; Biedermann, Peter H. W.; Besana, Laura; Battisti, Andrea; Rassati, Davide (Frontiers in Microbiology, 2025)
Ambrosia beetles (Curculionidae: Scolytinae and Platypodinae) are wood-boring insects studied as examples of fungus-insect symbiosis and for their success as invasive species. While most research on their microbiota has focused on fungal associates, their bacterial communities remain largely understudied. In this review, we synthesize current knowledge on the bacterial microbiota of ambrosia beetles, identify critical gaps in the field, and provide recommendations for future research. To date, eight metabarcoding studies have explored bacterial communities in ambrosia beetles, analyzing a total of 13 species, mostly within the tribe Xyleborini (Scolytinae). These studies have examined the presence of bacteria in ambrosia beetle mycetangia, organs specialized for transporting fungal symbionts, as well as bacterial diversity in fungal gardens and whole beetles, across different life stages, and under varying environmental conditions. In general, bacterial communities appear to be highly specific to the beetle species, and differ between the beetles and their fungal gardens. Most studies employed 16S rRNA gene metabarcoding, and the optimal primer combination for characterizing bacterial communities in environmental samples is 515F/806RB (V4). Various methods for collecting beetles have been used, such as ethanol-baited traps, direct collection from galleries, logs kept in emergence cages, and rearing, but which of them to select when planning a study depends on the specific aim. A significant knowledge gap remains regarding the functional roles of dominant bacterial taxa, as metabarcoding studies often assume that these roles are similar to those played in other beetle species, such as bark beetles. More studies should be conducted to test hypotheses regarding the various factors influencing microbial composition and function, and advanced molecular techniques, including (meta-) genome and transcriptome sequencing, which have been employed in only a limited number of studies, could offer great potential to help bridging this knowledge gap.